Ben Cao Gang Mu. - Li, Shizhen (University of California Press, 2024)
Volume I is divided into two parts. Part A of volume 1 in the Ben cao gang mu series offers a translation of chapters 1 and 2 and portions of chapter 3. Chapters 1 and 2 are devoted to introducing the history of materia medica. Chapter 3 is devoted to pharmaceutical drugs for diseases. Chapter 3 is continued, along with chapter 4, in part B of volume I. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of.
Keywords: Medicine, Chinese -- Early works to 1800.; Materia medica -- China -- Early works to 1800.; Médecine chinoise -- Ouvrages avant 1800.; Matière médicale -- Chine -- Ouvrages avant 1800.; MEDICAL / Acupuncture.; Materia medica; Medicine, Chinese; Drugs, Chinese -- Herbal.; China; Early works